PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 7 PADANG - Fitri, Rahayu; Emidar, Emidar; Rasyid, Yulianti (Universitas Negeri Padang, 2018)
ABSTRACTÂ This article was written to determine the effect of discovery learning model assisted by audiovisual media on the ability to write fable text by students of class VII SMPN 7 Padang. The data of this research is the score of writing ability of fable text. Data were collected by giving performance test of fable test writing ability on sample before and after applying discovery learning model assisted by audiovisual media. The ability to write fable text before and after applying a discovery learning model is aided by audiovisual media rather than to see the effect by using the t-test formula. The results showed that (1) the ability of writing fable text by grade VII students of SMPN 7 Padang before applying the discovery learning model aided by audiovisual media is on the Qualification More than Enough (Ldc) with the average value of 67,08, (2). the ability to classify fable by grade VII students of SMPN 7 Padang after applying discovery learning model assisted by audiovisual media with good qualification (B) with score average 76,53, and (3) based on t-test, alternative hypothesis accepted at significant level 95% and degrees of freedom due to thitung> ttable (2.80> 1.70).Â Kata kunci: Model discovery learning, media audiovisual, teks fabel